Exploring ozonation as treatment alternative for methiocarb and formed transformation products abatement. (November 2017) - Cruz-Alcalde, A.; Sans, C.; Esplugas, S.
Abstract: Despite the high toxicity and resistance to conventional water treatments exhibited by methiocarb (MC), there are no reports regarding the degradation of this priority pesticide by means of alternative purification technologies. In this work, the removal of MC by means of ozonation was studied for the first time, employing a multi-reactor methodology and neutral pH conditions. The second-order rate constants of MC reaction with molecular ozone (O3 ) and formed hydroxyl radicals (OH·) were determined to be 1.7·10 6 and 8.2·10 9  M −1  s −1, respectively. During degradation experiments, direct ozone reaction was observed to effectively remove MC, but not its formed intermediates, whereas OH· could oxidize all species. The major identified TPs were methiocarb sulfoxide (MCX), methiocarb sulfoxide phenol (MCXP) and methiocarb sulfone phenol (MCNP), all of them formed through MC oxidation by O3 or OH· in combination with hydrolysis. A toxicity assessment evidenced a strong dependence on MCX concentration, even at very low values. Despite the OH· capability to degrade MC and its main metabolites, the relative resistance of TPs towards ozone attack enlarged the oxidant dosage (2.5 mg O3 /mg DOC) necessary to achieve a relatively low toxicity of the medium. Even though ozonation could be a suitable technique for MC removal from water compartments, strategies aimed to further promote the indirect contribution of hydroxyl radicals during this process should be explored. Graphical abstract: Highlights: MC showed high reactivity with both molecular ozone and formed hydroxyl radicals. The generation of TPs equally or even more toxic than MC was observed. Changes in toxicity were associated to the concentration of a major TP, MCX. Ozone could only degrade MC, whereas hydroxyl radicals oxidized all species. Indirect reaction must be favored to ensure MC removal and toxicity abatement.